(untitled) (Research, Society and Development, 2022)
The new Coronavirus pandemic established a global state of emergency and affected all regions of the world. However, the impact reached different proportions in each country and there were numerous factors that conditioned the intensity of the effects. The objective of the study was to discuss Covid-19 in Brazil in order to interpret indicators of the impact of the pandemic from the analysis of three perspectives: the biopolitical choices of confrontation, the management of necropolitical devices, and the neoliberalist scenario of violations to human rights. The method used was qualitative, in which the results of the indicators were analyzed from the theoretical perspectives of Mbembe’s bio and necropower, contextualized in the neoliberal economic model. The findings showed that the Brazilian lethality rate was above the averages of other regions of the world in almost the entire period observed. Most hospitalizations for Covid-19 in Brazil were of white people, however, it was black or brown people who showed the most symptoms of the disease. In the first quarter of 2021, the unemployment rate according to race/color was higher for black people compared to white people and, according to sex, it was higher for women compared to men. The biopolitics implemented worsened the consequences of the pandemic in Brazil, enhancing the segregation of those who can die and those who cannot die in a true necropolitical movement typical of the global south.